2023
DOI: 10.54319/jjbs/160218
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint Calculation of Net CO2 in Agroforestry and Agroindustry of Gayo Arabica Coffee, Indonesia

Abstract: Carbon dioxide (CO2) in the atmosphere occurs as the result of various chemical, physical, and biological processes. The presence of CO2 around atmosphere greatly affects the agroforestry and agroindustry of coffee. This study aimed to describe the CO2 cycle in agroforestry and agroindustry of Gayo Arabica coffee (Coffea arabica) and net CO2 ha -1 of coffee plantation. CO2 cycle was analyzed based on the movement of CO2 around the agroforestry and agroindustry of coffee. CO2 cycle model describes net CO2, CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In future research, the application of PGPR should be combined with organic fertilizer. Several researchers [36][37][38][7][8][9] stated that soil organic matter content will increase and can be used as an energy source for the growth maintenance of microorganism cells and the production of extracellular enzymes. Components of cellulose and lignocellulosic organic matter are broken down into simple carbohydrates such as glucose for growth.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In future research, the application of PGPR should be combined with organic fertilizer. Several researchers [36][37][38][7][8][9] stated that soil organic matter content will increase and can be used as an energy source for the growth maintenance of microorganism cells and the production of extracellular enzymes. Components of cellulose and lignocellulosic organic matter are broken down into simple carbohydrates such as glucose for growth.…”
Section: Future Researchmentioning
confidence: 99%
“…Several factors can increase production, one of which is the use of fertilizers. However, the continuous and unbalanced use of inorganic fertilizers results in damage to soil structure, compaction, decreased nutrient content, environmental pollution due to accumulation of chemical residues, and disruption of the growth of microorganisms in the soil [7][8][9]. Therefore, it is necessary to use nanotechnology biofertilizers produced from microorganisms of the genus Pseudomonas, Enterobacter, Azospirilum, Azotobacter, Burkholderia, Bacillus and Serratia which can cooperate with plants in nutrient absorption as a Plant Growth Promoting Rhizobacteria (PGPR) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of rind surface cracking is due to faster cell growth in the fruit center than in rind, a sufficient amount of water should accelerate the process, forming more distinctive net patterns on the rind. Future research should be carried out in locations with low soil fertility which is expected to show mixed research performance between organic fertilizers (liquid and solid) and PGRs [17][18][19][20][21]. Likewise, the aim of farmers' self-reliance should be studied using local PGRs and liquid and solid organic fertilizers produced locally by farmers [34][35][36][37][38][39][40][41].…”
Section: Organoleptic Testmentioning
confidence: 99%
“…Based on the functions of organic fertilizers and growth hormones, it is necessary to combine the two to be applied to melon cultivation to increase the quality of melons. Several previous studies [17][18][19][20][21] recommended mixed research between PGRs and organic fertilizers (solid and liquid). With these considerations, this research was conducted to see how well organic fertilizers containing gibberellin and coconut water as natural PGRs work in the quality enhancement of muskmelon.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies related to sustainability evaluation in coffee were reported, such as a comprehensive sustainability evaluation of coffee production considering the environmental, energy, and economic impacts at the farm level according to fertilizer application in Indonesia [9]. Globally, studies related to the impact of coffee production on sustainability were also performed in other countries [1,10], such as Brazil, where the environmental impact of green coffee production was identified [11]. A study in Japan investigated the carbon footprint of coffee production [12], while another study determined the environmental impact of coffee production in India [13].…”
Section: Introductionmentioning
confidence: 99%